MONITORING PRIMARY SCHOOL STUDENTS' READING SKILLS THROUGH THE EGRA-U MOBILE APPLICATION - Diyora Ne’matova Baxodir kizi,Samadova Mohiroʻza (International Journal of Literature and Language Studies, 2026)
This study examines how the "EGRA-U" mobile application helps monitor and improve reading literacy in primary schools. The Early Grade Reading Assessment (EGRA) is a standard tool for testing early reading skills, but traditional paper tests take too much time to grade and analyze. To fix this, we developed the EGRA-U mobile app to automate the testing process based on international standards. We tested this app with primary school students over 12 weeks. The students were split into two groups: an experimental group using the app and a control group using traditional paper tests. The results show that students tracked with the EGRA-U app made faster progress in reading fluency and text comprehension. The app gave teachers immediate data, allowing them to help struggling students right away.